2020
DOI: 10.46903/gjms/18.01.1949
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Age Wise Distribution, Presentation and Successful Removal and Mortality of Foreign Body Aspiration Using Rigid Bronchoscope in Children of District D.I.KHAN, Pakistan

Abstract: Background: Foreign body aspiration commonly occurs in young children and is associated with high degree of mortality and morbidity. The objectives of this study were to determine epidemiologic, clinical and endoscopic perspectives of foreign body aspiration in children of District D.I.Khan, Pakistan. Materials & Methods: This descriptive study was conducted in Department of ENT, Gomal Medical College/ DHQ Teaching Hospital, D.I.Khan, Pakistan from November 2017-April 2019. 105 children with suspected fore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…We have arranged our research/ study as per design of "Marwat's Logical Trajectory for Research Process", [20][21][22][23][24][25][26][27] giving this effort a rational flow and including to sort out our research problems, knowledge gaps, converting research problems into research questions and research objectives, making research hypotheses and doing collection, analysis and interpretation of relevant data.…”
Section: Distribution Of Dr-tb By Outcome Of Treatment (Rq 10)mentioning
confidence: 99%
“…We have arranged our research/ study as per design of "Marwat's Logical Trajectory for Research Process", [20][21][22][23][24][25][26][27] giving this effort a rational flow and including to sort out our research problems, knowledge gaps, converting research problems into research questions and research objectives, making research hypotheses and doing collection, analysis and interpretation of relevant data.…”
Section: Distribution Of Dr-tb By Outcome Of Treatment (Rq 10)mentioning
confidence: 99%
“…55.2% of these non-fatal choking cases in children <4 years of age 4 . A descriptive cross-sectional study conducted in Department of ENT, Gomal Medical College/ DHQ Teaching Hospital, Pakistan,105 children with suspected FBA was included and found that FBA was present in 22.10% of age group 0-2 years, 63.95% of age 2-5 years and 13.95% of age 5-14 years 5 . Parental awareness regarding signs and symptoms of aspiration is important in the initiation of treatment.…”
Section: Introductionmentioning
confidence: 99%